2020
DOI: 10.1002/cncr.32699
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐based circulating tumor DNA mutations as a diagnostic and prognostic biomarker for lung cancer

Abstract: Background The objectives of the current study were to develop an initial blood‐based circulating tumor DNA (ctDNA) gene signature and to validate the clinical test performance in patients with early primary and secondary lung cancer. Methods Between January 2009 and October 2014, a total of 211 patients with known or suspected lung cancer donated their blood prior to surgery and were followed up to May 2018. ctDNA was extracted from plasma and from corresponding formalin‐fixed, paraffin‐embedded tissues. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…There are several techniques to detect ctDNA, including PCR-based (7,23), NGS panel based, and be spoked NGS (10). In this study, using a next-generation sequencing (NGS)-based panel test for cfDNA analysis, we found that detecting mutations in cancer-related genes from postoperative ctDNA (POD 3-12) predicted poor patient outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are several techniques to detect ctDNA, including PCR-based (7,23), NGS panel based, and be spoked NGS (10). In this study, using a next-generation sequencing (NGS)-based panel test for cfDNA analysis, we found that detecting mutations in cancer-related genes from postoperative ctDNA (POD 3-12) predicted poor patient outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…Detecting mutations in EGFR, including the T790M resistant mutation, is already used for clinical decision-making in advanced NSCLC patients (6). It has been reported that ctDNA analysis prior to the surgery in early-stage lung cancer patients can detect somatic mutations in tumors at high sensitivity and specificity (7), and that ctDNA analysis is able to detect mutations which will present even in a heterogeneous manner in tumor tissues (8,9). Additionally, recent studies have suggested that ctDNA can be a potential biomarker for the assessment of post-surgical MRD (10), as well as a potential predictor for the disease progression prior to radiological modalities (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a prospective study involving 16,890 participants, the methylation marker cg10673833 was selected and identified as an early diagnostic marker for high-risk patients with colorectal cancer, with high specificity (86.8%) and sensitivity (89.7%). Leung et al [ 91 ] detected the highest frequency of EGFR, KRAS, and TP53 mutations in the ctDNA of 166 patients with lung cancer. In terms of cancer diagnosis, compared with conventional clinicopathological results, the ctDNA diagnosis had a 98% positive predictive ability, 89% specificity, and 85% sensitivity, but the negative predictive value was 35%, which is a serious and urgent problem that should be solved.…”
Section: Clinical Application Of Ctdna During Cancer Progressionmentioning
confidence: 99%
“…Leung et al [ 28 ] demonstrated the usefulness of ctDNA as a diagnostic test in patients with early stage NSCLC, analyzing the presence of EGFR , KRAS , and p53 mutations, mostly frequent in adenocarcinoma and epidermoid lung carcinoma. When compared to the analysis of neoplastic tissue obtained with standard invasive procedures, this method showed comparable results, with a specificity of 89% in confirming the diagnosis.…”
Section: Diagnostic and Prognostic Value Of Circulating Biomarkersmentioning
confidence: 99%